Decoction derived from Allium ascalonicum L. bulbs and Sojae Semen Praeparatum alleviates wind-cold-type common cold via Nrf2/HO-1 pathway and modulation of Lactobacillus murinus level - Yuanyuan Jiang; Yuanyuan Jiang; Yuanyuan Jiang; Wenfeng Wei; Jiaxin Zhou; Jiaxin Zhou; Jiaxin Zhou; Shixian Qiu; Shixian Qiu; Shixian Qiu; Qixin Yang; Qixin Yang; et al. (Frontiers Media S.A., 2024)
BackgroundCong-Chi decoction (CCD) is made using Allium ascalonicum L. (shallot) bulbs and Sojae Semen Praeparatum (SSP). Shallot bulbs and SSP are both used regularly in traditional Chinese medicine; however, there are no recent pharmacological studies on their synergistic effects. Despite their roles in the treatment of the common cold for thousands of years, their pharmacological mechanisms of action against wind-cold-type common cold are yet to be explored comprehensively.MethodsA mouse model was standardized using wind-cold modeling equipment to study the anti-inflammatory, antioxidant, and antiapoptotic effects of CCD. Then, 16S rRNA sequencing was employed to analyze the association between Lactobacillus murinus and changes in body temperature. Additionally, the antipyretic effects of L. murinus were validated via animal experiments.ResultsThe results indicate that CCD improves the symptoms of wind-cold by reducing fever, levels of pro-inflammatory factors, and cellular apoptosis, as well as increasing the blood leukocyte and lymphocyte counts, thereby alleviating lung tissue damage. The effects of CCD are mediated by upregulation of pulmonary Nrf2 and HO-1 expressions, thereby reducing oxidative damage in the lungs, in addition to other anti-inflammatory mechanisms. Furthermore, CCD increases the abundance of L. murinus in the intestinal tract. The animal experiments confirm that L. murinus ameliorates fever in mice.ConclusionCCD exhibits remarkable antioxidant and anti-inflammatory properties for effectively treating wind-cold-type common cold. Furthermore, its regulatory effects on L. murinus represent a novel mechanism for product development.